2002
DOI: 10.1002/pri.252
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of a single chest physiotherapy treatment on mechanically ventilated patients with acute lung injury

Abstract: Patients with acute lung injury are notably complex to nurse and may require protracted physiotherapy intervention, which may take many forms. As de-recruitment was the single most important event that occurred in the present study population, a prescriptive chest physiotherapy approach to treating mechanically ventilated patients with acute lung should be questioned and adapted accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 20 publications
2
37
0
6
Order By: Relevance
“…37 Differences in heart rate were not significant between the groups in any of these studies. Similarly, 3 studies that assessed mean arterial pressure (one good quality study of Flutter vs usual care in mechanically ventilated ICU subjects, one fair quality study of IPV vs CPT in COPD subjects, and one poor quality study comparing CPT regimens in mechanically ventilated subjects) reported no significant group differences.…”
Section: Signs and Symptomsmentioning
confidence: 63%
See 4 more Smart Citations
“…37 Differences in heart rate were not significant between the groups in any of these studies. Similarly, 3 studies that assessed mean arterial pressure (one good quality study of Flutter vs usual care in mechanically ventilated ICU subjects, one fair quality study of IPV vs CPT in COPD subjects, and one poor quality study comparing CPT regimens in mechanically ventilated subjects) reported no significant group differences.…”
Section: Signs and Symptomsmentioning
confidence: 63%
“…The evidence we reviewed indicates that airway clearance techniques are probably safe for ventilated ICU patients, and confer zero to small benefit to some clinical outcomes. 18,[21][22][23]28,[33][34][35][36][37] Consideration may be given to the use of airway clearance techniques for ventilated ICU patients, to reduce the risk of acquiring pneumonia, based upon 2 studies, which included 76 subjects. 23,27 Based on the current limited evidence, airway clearance modalities might not be recommended as routine prophylaxis to prevent postoperative pulmonary complications in adults.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations